2020
DOI: 10.1177/0300060520947918
|View full text |Cite
|
Sign up to set email alerts
|

Mixed adenoneuroendocrine carcinoma (MANEC) of the ampulla of Vater in a Chinese patient: A case report

Abstract: Mixed adenoneuroendocrine carcinoma (MANEC) is a rare tumour of the gastrointestinal tract with both epithelial and neuroendocrine components. We describe a case of a 57-year-old man who presented with yellow sclera and dark urine. Contrast-enhanced computed tomography (CT) showed enlargement of the intra and extrahepatic bile ducts and a neoplastic lesion at the end of the common bile duct which was indistinguishable from the adjacent head of the pancreas and duodenum. A pancreaticoduodenectomy was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…MiNEN is a rare tumor commonly found in the appendix and colorectum in the digestive tract, while MiNENs that occur in the ampulla are very rare. The literature search found only 16 cases,and most of them were case reports[ 1 , 2 , 5 ]. Patients with a MiNEN of the ampulla usually present with nonspecific clinical symptoms, such as abdominal pain, jaundice, nausea, vomiting, and upper abdominal discomfort[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiNEN is a rare tumor commonly found in the appendix and colorectum in the digestive tract, while MiNENs that occur in the ampulla are very rare. The literature search found only 16 cases,and most of them were case reports[ 1 , 2 , 5 ]. Patients with a MiNEN of the ampulla usually present with nonspecific clinical symptoms, such as abdominal pain, jaundice, nausea, vomiting, and upper abdominal discomfort[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the best treatment for MiNEN is not clear[ 5 ]. It has been reported that for MiNEN without distant metastases, radical surgery can be the first choice for treatment, and palliative chemotherapy can be selected when the patient has distant metastases[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 19 cases of NENs reported in the literature in a two-year time period, from May 2020 until April 2022 ( Table 1 ) [ 9 , 14 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…HE-stained sections served for the morphological identification of both neuroendocrine and nonneuroendocrine components. Immunohistochemistry is mandatory to test the nature of the neuroendocrine component, which is also recommended to evaluate the subtype of the nonneuroendocrine (11)(12)(13)15,16,19,20,22,23,25). Preoperative diagnosis was rarely established, and only a few cases reported had been diagnosed through preoperative biopsy with endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) specimens (17)(18)(19)21,24).…”
mentioning
confidence: 99%